Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, Dan Kecerdasan Spiritual Terhadap Kinerja Karyawan Di Puskesmas Ciptomulyo Kota Malang - Mochammad Taufik; Jeni Susyanti; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study is to explain how emotional intelligence, intellectual intelligence, and spiritual intelligence can partially and simultaneously affect employee performance.The research method is quantitative and the type of research is explanatory research. The sample in the study was 46 Ciptomulyo Health Center employees. In collecting data using a questionnaire and the methods in the analysis are instrument test, normality test, multiple regression analysis, hypothesis testing with SPSS tools.The results of the study, namely emotional intelligence, intellectual intelligence, and spiritual intelligence together have a significant influence on the performance of Ciptomulyo Health Center employees. While partially showing emotional intelligence, intellectual intelligence, and spiritual intelligence have no effect on performance. Keywords: Emotional Intelligence, Intellectual Intelligence, Spiritual Intelligence, and Employee Performance.